Chaucer's losers, Nintendo's children, and other forays in queer ludonarratology - Pugh, Tison (Frontiers of narrative., 2019)
Tison Pugh examines the intersection of narratology, ludology, and queer studies, pointing to the ways in which the blurred boundaries between game and narrative provide both a textual and a metatextual space of queer narrative potential. By focusing on these three distinct yet complementary areas, Pugh shifts understandings of the way their play, pleasure, and narrative potential are interlinked. Through illustrative readings of an eclectic collection of cultural artifacts--from Chaucer's Canterbury Tales to Nintendo's Legend of Zelda franchise, from Edward Albee's dramatic masterpiece Who's Afraid of Virginia Woolf? to J.K. Rowling's Harry Potter fantasy novels--Pugh offers perspectives of blissful ludonarratology, sadomasochistic ludonarratology, the queerness of rules, the queerness of godgames, and the queerness of children's questing video games. Collectively, these analyses present a range of interpretive strategies for uncovering the disruptive potential of gaming texts and textual games while demonstrating the wide applicability of queer ludonarratology throughout the humanities.